2012
DOI: 10.1074/mcp.m111.008755
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Proteomic Profiles During the Process of Anti-Thy1 Nephritis

Abstract: Anti-Thy1 nephritis is a well-established experimental mesangial proliferative nephritis model. Exploring the molecular mechanisms of pathophysiology in anti-Thy1 nephritis may elucidate the pathogeneses of mesangial proliferation. We examined the roles and acting mechanisms of differentially expressed proteins (DEPs) by bioinformatics analysis of glomeruli proteomic profiles during the course of anti-Thy1 nephritis. In total, 108 DEPs were found by two-dimensional fluorescence difference gel electrophoresis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Glomerular proteomic profiling revealed that Nit2 is significantly decreased during the course of antiarthritic-Thy1-induced nephritis in adult male Wistar rats (Lu et al 2012). However, the biological significance of these findings is unknown.…”
Section: Proteomic Analysis Of Nit2/ω-amidasementioning
confidence: 99%
“…Glomerular proteomic profiling revealed that Nit2 is significantly decreased during the course of antiarthritic-Thy1-induced nephritis in adult male Wistar rats (Lu et al 2012). However, the biological significance of these findings is unknown.…”
Section: Proteomic Analysis Of Nit2/ω-amidasementioning
confidence: 99%
“…Traditional anti-Thy-1 nephritis is a classic, reversible model of MesPGN. Certain studies have shown that 2-3 days after antibody injection, rat kidneys demonstrate acute mesangial injury that primarily results in mesangial dissolution and mesangial cell apoptosis [16,17]. The MesPGN model induced by HSV injection (Habu nephritis) is a self-limiting nephritic model that results in acute focal damage and mesangial cell proliferation in rats, rabbits and mice [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study regarding the gene expression profiles in an antiThy-1 nephritic model, the results revealed significantly increased expression levels of inflammation-related factors, including the chemokines CCL2, CXCL10 and CXCL13 and the cell adhesion molecules ICAM1 and VCAM1, suggesting that the upregulation of inflammationrelated factors is associated with anti-Thy-1 nephritic pathological processes [16,17]. Because the role of CCL2 has been well documented in human and rat MesPGN, we selected CXCL10 to explore the roles of chemokines in the MesPGN pathological process in mice.…”
Section: Mxi1 −/− Mice Exhibit Significantly High Cxcl10 Expressionmentioning
confidence: 92%
See 1 more Smart Citation
“…Proliferative mesangial models, including the rat acute anti-Thy1 nephritis model and mouse snake venom-triggered glomerulonephritis, are characterised by initial mesangiolysis, followed by mesangial cell proliferation and accumulation of mesangial matrix, in turn causing proteinuria. The conditions subsequently resolve, and the histology becomes almost normal [9,12]. Membranous nephropathy models, such as the passive Heymann nephritis model (PHN), are characterised by the formation of membrane attack complexes inducing injury to podocytes and expansion of the glomerular basement membrane, in turn causing high-level proteinuria [10,27].…”
mentioning
confidence: 99%